(untitled) (Linguostylistic Studies, 2018)
The article analyzes the theoretical and practical aspects of the semantic-syntactic peculiarities of the dependent components of the predicatives of state. The study has revealed that the semantic-syntactic dependence of the components of the semantic-syntactic structure of a simple sentence is their specificity to depend on the predicates of a sentence. The predicatives of state determine the semantic-syntactic dependence on the state of a subject and reflect the independent autonomous features of the subject. Predicatives of state are focused on the passive subject. In some cases these predicatives manifest their dependence on the object. Predicatives of state form the following main groups according to the semantic criteria: 1) the predicates expressing the physical condition by predicative adverbs boliache, vazhko, dushno, zharko, lehko, morozno, mlosno, teplo, tiazhko, kholodno etc.; 2) expressing the physical condition by the verbs: badorytysia, dryzhaty, drimaty, lykhomanyty, maryty, nezduzhaty, nudyty, sknity, slabuvaty, temperaturyty, terpity, tremtity, triasty; 3) designation of the emotional and psychological state, psychophysical feelings of the person by the predicative adverbs vazhko, veselo, vidradno, kryvdno, lehko, liachno, radisno, smishno, soromno, strashno, sumno, tiazhko; 4) designation of the emotional and psychological state, psychophysical feeling of the person by predicate nouns bida, hrikh, dyvo, dosada, zhal, lin, sorom; 5) designation of the emotional and psychological state, psychophysical feelings of the person by the verbs bentezhyty, vahatysia, hnivatysia, kokhaty, nenavydity, pechalytysia etc.; 6) expression of the intellectual state by predicative adverbs vidomo, zrozumilo, nezrozumilo, sumnivno etc.; 7) expression of the intellectual state by verbs znaty, vvazhaty, pamiataty, rozumity etc. The predicatives of state form the sentence constructs in which the semantic-syntactic dependence of the subject of state is actualized. The above-mentioned groups of the dependent components of predicative of state are considered on the materials from the prose works by Iosyp Strutsiuk. The lexical range of the expression of dependent components in the prose of Joseph Strutsuk covers multifaceted semantic groups. Further research is suggested to study the dependent components of the formal-syntactic sentence structure, which are based on syntactic relationships.